The Analisis Perubahan Land Use dan Land Cover di Desa Ciwaruga menggunakan Citra Satelit Landsat-8, Sentinel-2A dan Pleiades - Faqikh, Achmad; Dzulfikar, Faiz; Fatima, Kalita Adelpha; Kurnia, Liqa Wapiq; Fyndiani, Saskia Syafinda; Alamsah, Shakti Aulia; Salamah, Sheren Siti; Somantri, Lili; Himayah, Shafira (Jurnal Pendidikan Geografi Undiksha, 2025)
Remote sensing is a technology used to obtain information about the earth or objects on the earth's surface through the capture and analysis of data from sensors located on satellite aircraft. The benefits of remote sensing are numerous, one of which is for mapping land use and land cover. In conducting this research, there are 3 types of images used, namely Landsat 2014 and 2024 images, Sentinel 2024 images, and Pleiades 2024 images. The reason for taking these three images for analysis and practicum is because the Landsat image has low spatial resolution, the sentinel image has medium spatial resolution, and the pleiades image has high spatial resolution. This difference can show the most effective image used to analyze land cover and land use in Ciwaruga Village. The accuracy test using Confusion Matrix and Kappa Index shows a good level of interpretation accuracy if it exceeds the predetermined standards. In this case, the use of high-resolution imagery, such as Pleiades, provides more detailed interpretation results.